MicroRNA-200a is up-regulated in aged rats with erectile dysfunction and could attenuate endothelial function via SIRT1 inhibition - Pan, Feng (Asian J Androl, 2016)
MiR-200a was shown to be upregulated in the corpus cavernosum (CC) of rats with aging-related erectile dysfunction (A-ED) in our previous study. Among its target genes, SIRT1 was also reported as a protective factor in erectile function by our groups previously. Thus, miR-200a might attenuate the erectile function in A-ED via SIRT1 inhibition. In the present study, three animal groups were included: aged rats with ED (group AE, n = 8), aged rats with normal erectile function (group AN, n = 8), and young rats as normal controls (group YN, n = 8). CCs from each group were collected for histological and molecular measurements to validate the dysregulation of miR-200a and SIRT1. After that, the cavernous endothelial cells (CECs) from CC of aged rats with normal erectile function were transfected with miR-200a in vitro. Then the expression of SIRT1 and molecules within the eNOS/NO/PKG pathway were measured to investigate whether the transfection could imitate the attenuated process of erectile function in the aged. As a result, miR-200a was upregulated while the SIRT1, the levels of eNOS and cGMP were all downregulated in the CCs from AE group. After transfection in vitro, the miR-200a was upregulated while the SIRT1 and levels of eNOS and cGMP were obviously downregulated. Finally, based on the results of our previous study, we further verify that up-regulation of miR-200a could participate in the mechanisms of A-ED via SIRT1 inhibition, and mainly attenuate endothelial function via influencing the eNOS/NO/PKGpathway.